Effect of estradiol during culture of bovine oocyte–granulosa cell complexes on the mitochondrial DNA copies of oocytes and telomere length of granulosa cells. Issue 4 (November 2014) - Endo, M.; Kimura, K.; Kuwayama, T.; Monji, Y.; Iwata, H.
Summary During the development of oocytes from early antral follicles (EAFs) to antral follicles (AFs), the mitochondrial DNA copy number (Mt DNA number) increases, and granulosa cells markedly proliferate. This study examined the effect of supplementation of culture medium with estradiol-17β (E2) on the in vitro growth of oocytes, and increases in the Mt DNA number, and telomere length during the in vitro culture of oocytes derived from EAFs (0.4–0.7 mm in diameter). The E2 supplementation improved antrum formation and the ratio of oocytes reaching the metaphase II (MII) stage, and there was a significant difference in these values between addition E2 concentrations of 10 μg/ml and 0.1 μg/ml. When the oocytes were cultured in the medium containing 10 μg/ml E2, the Mt DNA number determined by real-time polymerase chain reaction (PCR) significantly increased, and the ratio of the Mt DNA number at the end of culture to the Mt DNA number at the beginning of the culture was greatly different among cows, and could be predicted by the degree of the difference between the Mt DNA number of oocytes derived from EAFs and that of oocytes derived from AFs (3–6 mm in diameter). When oocytes were cultured for 16 days in a medium containing 10 μg/ml E2 or 0.1 μg/ml E2, the Mt DNA number of oocytes grown in vitro did not differ, but the telomere length of the granulosa cells was significantly greater in the 10 μg/ml E2 group than in the 0.1 μg/ml group. In conclusion, E2 supplementation in culture medium improved the growth of oocytes derived from EAFs, and a high E2 concentration increased the telomere length of the granulosa cells.